Extractive Spectrophotometric Determination of Palladium(II) Using 3-Phenoxy Benzaldoxime - Lokhande, R.S.; Namade, H.G.; Chaudhry, A.B.; Hudiwale, D.G. (Asian Journal of Chemistry, 2010)
3-Phenoxy benzaldoxime was synthesized and its characterization was carried out using FT-IR and NMR technique. The reagent was then used for the development of new method for the extractive spectrophotometric determination of Pd(II) metal. The reagent reacts with the metal to produce yellow coloured complex which was then extracted into chloroform at pH 4.0 having absorption maxima at 435 nm and obeys Beer's law over a range of 0.4 to 40 μg/mL of palladium(II); the molar absorptivity being 2.434 x 103 L mol-1 cm-1. The developed method was then applied for the determination of Pd(II) metal in palladium catalyst and synthetic mixtures. Interferences of the foreign ions have also been studied.